Ecotoxicity and Sustainability of Emerging Pb‐Based Photovoltaics - Lu, Xingwen; Yan, Dong; Feng, Jiangtao; Li, Meng; Hou, Bo; Li, Zhe; Wang, Fei (Solar RRL, 2022)
Emerging Pb‐based photovoltaic (PV) technologies, including in particular solution processed halide perovskite solar cells (PSCs) and Pb chalcogenide quantum dot solar cells (QDSCs), are among the most promising next‐generation PV technologies for a range of disruptive energy and electronic applications. However, the potential toxicity and leakage of hazardous Pb species have become one of the main barriers to their large‐scale application. When solar cells are subject to physical damage or failure of encapsulation, rapid leakage of Pb may occur, which can be accelerated by exposure to external environmental weathering conditions such as rainfall and elevated temperature. Herein, an in‐depth investigation on the essential role of Pb in PSCs and QDSCs, as well as common causes of Pb leakage, is undertaken. The hazardous effects of Pb toxicity on soil plants, bacteria, animals, and human cells are also evaluated. Recent progress in developing effective strategies for Pb leakage reduction, such as Pb‐free or Pb‐less perovskite materials, device architecture design, encapsulation absorbers for PSCs, and core–shell structure and ligand exchange method for QDSCs, in addition to Pb recycling strategies of end‐of‐life solar cells are summarized. This review provides quantitative insights into the future development of eco‐friendly emerging Pb‐based PV technologies. This review provides a unique vision of the ecotoxicity and sustainability of emerging Pb halide perovskite solar cells and Pb chalcogenide quantum dot solar cells. The critical role of Pb, the causes of Pb leakage, the hazardous impact, Pb leakage reduction strategies, and Pb recycling strategies of end‐of‐life solar cells are systematically analyzed.